Understanding the Diffusion of Ambulatory Surgery Centers - Suskind, Anne M. (Surg Innov, 2014)
BACKGROUND: Outpatient surgery is increasingly delivered at freestanding ambulatory surgery centers (ASCs), which are thought to deliver quality care at lower costs per episode. The objective of this study was to understand potential facilitators and/or barriers to the introduction of freestanding ASCs in the United States. METHODS: This is an observational study conducted from 2008–2010 using a 20% sample of Medicare claims. Potential determinants of ASC dissemination, including population, system, and legal factors, were compared between markets that always had ASCs, never had ASCs, and those that had new ASCs open during the study. Multivariable logistic regression was used to determine characteristics of markets associated with the opening of a new facility in a previously naïve market. RESULTS: New ASCs opened in 67 previously naïve markets between 2008 and 2010. ASCs were more likely to open in HSAs that were urban (adjusted OR 4.10; 95% CI 1.51–10.96), had higher per capita income (adjusted OR 3.83; 95% CI 1.43–10.45), and had less competition for outpatient surgery (adjusted OR 2.13; 95% CI 1.02–4.45). Legal considerations and latent need, as measured by case volumes of hospital-based outpatient surgery in 2007, were not associated with the opening of a new ASC. CONCLUSIONS: Freestanding ASCs opened in advantageous socioeconomic environments with the least amount of competition. Because of their associated efficiency advantages, policymakers might consider strategies to promote ASC diffusion in disadvantaged markets to potentially improve access and reduce costs.